Smart Building Security using ESP32 based AES One Bio-key and Owner's Biometrics Encryption Technology. - Radhi, Batool M.; Hussain, Mohammed A. (Journal of Basrah Researches (Sciences), 2023)
Internet of Things (IoT) connects smart devices to the internet, but it poses significant security challenges. ‘Security measures like access control, authentication, and encryption must be implemented during IoT system development to safeguard sensitive information and ensure secure transmission. Regular security updates, ongoing assessment, and improved measures are necessary to address evolving threats. Data security is crucial for overall IoT system security, given its unique features like perception, transmission, and processing. In this paper, it is suggested using encryption for data sent over Wi-Fi to improve Internet of Things (IoT) security. Advanced Encryption Standard (AES) commonly used encryption standard, and it is the encryption technique employed. AES algorithm uses one bio-key (variable key every minute) to maximize security and the capacity to fend off attacks. It is added the owner's biometric to the bio-key for authentication and security in order to authenticate the system. Our technology stands out with robust encryption and authentication against numerous assaults because the owner's biometrics are encrypted and it is added to the bio-key made up of the minute-by-minute changes to the year, month, day, hour, and minute. The data is encoded in ESP32 and sent to the local server and then stored in a Python language database using the HTTP protocol. The database is hosted on XAMPP, which is a web server package that allows easy database management.